2016
DOI: 10.1016/j.ijhydene.2016.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid plasma-catalytic methanation of CO2 at low temperature over ceria zirconia supported Ni catalysts

Abstract: International audienceA hybrid plasma-catalytic system was used in for the hydrogenation of carbon dioxide (CO2) into methane (methanation) at atmospheric pressure and very low temperature using a dielectric barrier discharge (DBD) plasma reactor packed with Ni-CexZr1−xO2 catalysts. Three catalysts were prepared by a conventional wet impregnation method, using 15 wt% of Ni loading over ceria-zirconia mixed oxides having different Ce/Zr ratios. The physico–chemical features of both catalysts and supports were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(69 citation statements)
references
References 28 publications
(41 reference statements)
3
57
1
Order By: Relevance
“…The equilibrium CO 2 conversion is reached at 340 • C. CO 2 -TPD profiles of Ni/CZ show weak and medium sites, different from Ni/Al 2 O 3 , which shows weak and strong basic sites; CO 2 adsorbed on strong basic sites cannot desorb from Ni/Al 2 O 3 surface until 700 • C. Consequently, the strongly adsorbed CO 2 on the surface does not participate in the reaction carried out from 220 • C to 400 • C. According to [166], CO 2 reacts with surface hydroxyls and surface oxygen to form hydrogen and monodentate carbonate, respectively [164,[166][167][168][169][170][171][172]. Formate species could be also important intermediates during the reaction [63,173,174].…”
Section: Silica-supported Nickelmentioning
confidence: 99%
“…The equilibrium CO 2 conversion is reached at 340 • C. CO 2 -TPD profiles of Ni/CZ show weak and medium sites, different from Ni/Al 2 O 3 , which shows weak and strong basic sites; CO 2 adsorbed on strong basic sites cannot desorb from Ni/Al 2 O 3 surface until 700 • C. Consequently, the strongly adsorbed CO 2 on the surface does not participate in the reaction carried out from 220 • C to 400 • C. According to [166], CO 2 reacts with surface hydroxyls and surface oxygen to form hydrogen and monodentate carbonate, respectively [164,[166][167][168][169][170][171][172]. Formate species could be also important intermediates during the reaction [63,173,174].…”
Section: Silica-supported Nickelmentioning
confidence: 99%
“…Additionally, dielectric barrier discharge (DBD) plasma is a simple technique for creating non‐equilibrium plasma conditions at low gas temperature and atmospheric‐pressure . Many efforts have been made to study the influence of DBD plasma on enhancing the catalytic performance . Bian and Fu studied the effect of DBD plasma on the catalyst for methanation and Fischer‐Tropsch synthesis respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, relatively high temperatures are needed to reach acceptable conversions. Recently, it was shown that a plasma DBD catalytic process can lead to high conversions of CO 2 and high CH 4 selectivity at temperatures lower than 200°C [3,7,8,9].…”
Section: Introductionmentioning
confidence: 99%